Prediction of material property parameter of FRP composites using ultrasonic and acousto-ultrasonic techniques - Srivastava V.K.; Prakash R. (My University, 2025)
A study has been made of the use of ultrasonic techniques and acousto-ultrasonic techniques to evaluate the material property parameter of the glass fibre reinforced plastic (GRP) and carbon fibre reinforced plastic (CFRP) composites. The theoretical results indicated that the ultimate tensile strength of GRP and CFRP composites can be related to the material property parameter of FRP composites. © 1987.